Bioactivity and genetic screening of marine actinobacteria associated with red algae Gelidiella acerosa - Maria Ulfah; Noer Kasanah; Niken Satiti Nur Handayani (Universitas Gadjah Mada, 2017)
Bacterial resistance to existing antibiotics has driven a search for new antibiotics from marine actinobacteria. Bioactivity and genetic screening of actinobacteria associated with red algae Gelidiella acerosa were conducted to discover new antibacterial compounds against Vibrio alginolyticus. A total of 14 actinobacteria isolates were obtained from G. acerosa. The isolates were subjected to genetic screening for nrps (non-ribosomal peptide synthetase) and FADH2-dependent halogenase genes. The isolates’ ability to produce secondary metabolites was examined by fermentation in various media in a six-well mini plate. The bioactivity of the secondary metabolites was screened using a microtiter assay and the agar overlay method. The results showed that all 14 isolates had the nrps gene, whereas none had the halogenase gene. Meanwhile, eight of the actinobacteria isolates showed antibacterial activity against V. alginolyticus.